(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Available incipient sediment motion models were mostly developed based on homogeneous non-cohesive sediment. In non-homogeneous sediment mixture, particularly with fraction of cohesive particles might have an effect on the values of incipient sediment motion using the available models. In this study the effects of weak cohesive material on the incipient motion of sand-silt mixture were investigated in laboratory and compared with different existing formulas. Fine sand with median grain size of d50=153 Âµm was used whilst the cohesive material is kaolinite-silt with d50=28 Âµm. The sand-silt mixtures were prepared with sand percentage (Sa)/Silt percentage (Si) distributions ranging from 100Sa/0Si to 0Sa/100Si. The condition for incipient sediment motion was defined in categories number 4 (i.e. frequent particle movement at nearly all locations) and number 6 (i.e. permanent particle movement at all locations) of 7 categories introduced by the Delft Hydraulic. Values of critical Shields parameter were monotonously increased as the percentage of silt increased but reached a relatively constant value as the silt percentage reached 50%. Comparing the data for the particular sediment range used in this study proved that the Brownlie, Van Rijn and Miedema relationships are capable to calculate the Shields parameter within the range of category 4 and 6